IMPLEMENTASI DAN STRATEGI PENGUATAN MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR - Putri Silalahi, Rachel Dewi; Rahma, Saskhia; Marpaung, Shofiatul Izza; Putri, Najwa Arisha; Hasibuan, Safaruddin (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to analyze the implementation of School-Based Management at UPT SDN 106163 Bandar Klippa and to formulate strengthening strategies based on actual conditions in the field. The research employed a qualitative approach using interviews. The research informants consisted of the principal and a fifth-grade teacher selected for their direct involvement in planning and implementing school programs. The findings indicate that the school has made efforts to apply the principles of School-Based Management through needs-based program planning, teacher involvement in decision-making, and the implementation of student character-building activities. However, the implementation has not yet been optimal due to limited funding, high administrative demands on teachers, and insufficient participation from the community and school committee.MThrough an idea engineering process, this study produced several strategies to strengthen School-Based Management, including simplifying teacher administrative tasks, optimizing task distribution, utilizing simple technologies to improve work efficiency, and enhancing collaboration among the school, committee, and parents. The study concludes that School-Based Management at the school has strong potential to improve, provided that key obstacles are addressed and all stakeholders demonstrate stronger commitment in supporting school governance.